p-type NiO hybrid visible photodetector - Mallows, John; Planells, Miguel; Thakare, Vishal; Bhosale, Reshma; Ogale, Satishchandra; Robertson, Neil (ACS Applied Materials & Interfaces, 2015)
A novel hybrid visible-light photodetector was created using a planar p-type inorganic NiO layer in a junction with an organic electron acceptor layer. The effect of different oxygen pressures on formation of the NiO layer by pulsed laser deposition shows that higher pressure increases the charge carrier density of the film and lowers the dark current in the device. The addition of a monolayer of small molecules containing conjugated pi systems and carboxyl groups at the device interface was also investigated and with correct alignment of the energy levels improves the device performance with respect to the quantum efficiency, responsivity, and photogeneration. The thickness of the Organic layer was also optimized for the device, giving a responsivity of 1.54 X 10(-2) A W-1 in 460 nm light.
Keywords: nickel oxide; organic; oxygen vacancies; photodetector; pulsed laser deposition; surface modifier

Humidity sensing and photodetection behavior of electrochemically exfoliated atomically thin-layered black phosphorus nanosheets - Erande, Manisha B.; Pawar, Mahendra S.; Late, Dattatray J. (ACS Applied Materials & Interfaces, 2016)
Recent investigations on two-dimensional black phosphorus material mainly highlight work on few atomic layers and multilayers. It is still unknown if the black phosphorus atomically thin sheet is an ideal structure for the enhanced gas solid interactions due to its large surface area. To further investigate this concern, we have synthesized few atomic layer thick nanosheets of black phosphorus using an electrochemical exfoliation method. The surface morphology and thickness of the nanosheet were identified using AFM, TEM, and Raman spectroscopy. The black phosphorus nanosheet thick film device was used for the gas sensing application with exposure to different humidites. Further, the few layer black phosphorus nanosheet based transistor shows good mobility and on/off ratio. The UV light irradiation on the black phosphorus nanosheet shows good response time. The overall results show that the few layer thick film of black phosphorus nanosheets sample exhibits creditable sensitivity and better recovery time to be used in humidity sensor and photodetector applications.
Keywords: black phosphorus; electrochemical exfoliation; humidity sensor; photodetector

Solvothermal growth of PbBi2Se4 nano-flowers: a material for humidity sensor and photodetector applications - Aher, Rahul; Bhorde, Ajinkya; Nair, Shruthi; Borate, Haribhau; Pandharkar, Subhash; Naik, Dhirsing; Vairale, Priti; Karpe, Smita; Late, Dattatray; Prasad, Mohit; Jadkar, Sandesh (Physica Status Solidi A-Applications and Materials Science, 2019)
In the present work, lead bismuth selenide (PbBi2Se4) nano-flowers are synthesized by using a simple solvothermal method. Humidity sensor and photodetector based on PbBi2Se4 nano-flowers are fabricated on indium tin oxide (ITO) substrates and their sensing properties are investigated. Formation of PbBi2Se4 is confirmed by XRD, EDS, and XPS whereas formation of nano-flowers is confirmed by SEM and TEM analysis. XRD analysis reveals the hexagonal crystal structure of PbBi2Se4 phase with a = b = 4.22 angstrom, and c= 17.42 angstrom. The surface morphology of PbBi2Se4 clearly shows the formation of well-organized flower-like nanostructures which closely resembles the shape of Dahlia. The elemental mapping of chemical constituents obtained from SEM-EDS analysis shows uniform distribution of chemical constituents for the Pb, Bi, and Se in PbBi2Se4 nano-flowers. The PbBi2Se4 nano-flowers based humidity sensor has a typical response time of approximate to 65s and recovery time of approximate to 75 s. In case of PbBi2Se4 nano-flowers-based photodetector, the response and recovery time are observed approximate to 121 and approximate to 123 s, respectively, under visible light illumination with photoresponsivity (5 x 10(-6)), photosensitivity (2.16%), and quantum efficiency (1.5 x 10(4)). The obtained results demonstrate the potential applications of solvothermally grown PbBi2Se4 nano-flowers-based devices for humidity sensors and photodetectors. The ease of the present work is to develop novel material to obtain device quality humidity sensors and photodetectors.
Keywords: humidity sensor; PbBi2Se4; photodetector; XPS; XRD

Entropy-driven reversible melting and recrystallization of layered hybrid perovskites - Rajput, Parikshit Kumar; Salunkhe, Parashurama; Sarma, Manmayuri; Basu, Meghasree; Gopal, Animesh; Joshi, Aprajita; Shingote, Ajinkya Sundarnath; Saha, Surajit; Rahman, Atikur; Nag, Angshuman (SMALL, 2024)
Keywords: hybrid perovskites; photodetector; reversible melting

High-performance photodetector from p-n junction of vertically aligned SnS2 and reduced graphene oxide - Das, Chayan; Kumar, Suresh; Dambhare, Neha V.; Kumar, Mahesh; Rath, Arup K.; Sahu, Satyajit (ACS Applied Electronic Materials, 2024)
Semiconducting 2D transition metal dichalcogenides (TMDC) became very popular in photodetection due to their high mobility and high rate of generating electron and hole pairs. Over the past decade, MoS2 and WS2 became the most popular TMDC for several applications. On the other hand, due to the complex synthesis process compared to MoS2 and WS2, SnS2 became a less popular 2D material for photodetection. We synthesized vertically aligned SnS2 flakes by a chemical vapor deposition (CVD) process with three temperature zones with controlled argon (Ar) gas flow. Pristine SnS2-based devices are not very suitable for photodetection applications because of their low photo-to-dark current ratio (I ph /I (dark) ), high response time, and low stability. So, they need to be decorated with oppositely doped materials. We decorated pristine SnS2-based devices with rGO nanoparticles, which significantly increased the device's performance. We found a high responsivity (R) of 1.33 A/W, detectivity (D) of 6.95 x 10(11) Jones, I ph /I dark of 102, and a rise time of 0.241 ms (fall time of 1.318 ms) with the rGO decorated SnS2-based device.
Keywords: 2D-SnS2; CVD; p-njunction; photodetector; rGO

WS2 nanoparticle-decorated, vertically aligned SnS2-based high-performance heterostructures for ambient-stable ultrafast photodetection - Das, Chayan; Kumar, Suresh; Sharma, Anjali; Kumar, Mahesh; Rath, Arup K.; Sahu, Satyajit (ACS Applied Nano Materials, 2025)
The development of visible-light photodetectors with high responsivity, rapid response, and long-term ambient stability remains a critical challenge in optoelectronics. Here, we report a high-performance photodetector based on a vertically aligned SnS2 film interfaced with WS2 nanoparticles, forming a p-n heterojunction. This device is fabricated using a scalable two-step method-chemical vapor deposition (CVD) for SnS2 growth and solution-based drop-casting for WS2 deposition-enabling precise control over the heterointerface, but trap states are inevitable due to the use of thermal CVD and the drop-casting method. The resulting photodetector exhibits remarkable optoelectronic characteristics, including a responsivity of 0.76 A/W, a detectivity of 7.56 x 10(11) Jones, a photo-to-dark current ratio of 119, and a fast rise time of 0.297 ms under visible illumination. These performance metrics are directly attributed to the optimized heterointerface, where the built-in electric field at the nanoscale WS2/SnS2 junctions promotes efficient charge separation and minimizes recombination losses. Notably, the device retains over 95% of its initial performance even after 1 week of ambient exposure, highlighting its superior environmental robustness. This work introduces an interface-engineering strategy that leverages the unique electronic properties of earth-abundant, nontoxic two-dimensional materials, offering a viable pathway for scalable, high-speed, and stable photodetectors suitable for next-generation optoelectronic systems.
Keywords: 2D; CVD; heterojunction; photodetector; SnS2; WS2